Analisis Pengaruh Situasi Kerja, Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Pada PT. Semen Baturaja (Persero) - Mietha Nella (Journal of Contemporary Public Administration, 2023)
The background of this research is to collect information and information about employees' perceptions of the workplace situation, job satisfaction and ongoing motivation and their relationship to employee performance. The purpose of this research is presented is to determine the effect of analysis: work situation, job satisfaction, motivation and environmental performance of employees of Pt. Semen Baturaja (Persero). This research was conducted at Pt. Semen Baturaja (Persero). Collecting information using a questionnaire, and taking the sample of this study as many as 65 employees with likelihood testing. Information analysis method used is multiple regression test, F test, and coefficient of determination (RÂ²). The results show that: 1). Partially the t-test variable Work Situation (X1) has an effect on employee performance at PT. Semen Baturaja (Persero). It is known from p-value less than 0.05.2). Partially, the variable job satisfaction t test (X2) has an effect on employee performance at PT. Semen Baturaja (Persero). It is known from the p value which is less than 0.05.3). Partially, the work motivation variable t test (X3) has no effect on employee performance at PT. Semen Baturaja (Persero). It is known from the p value greater than 0.05. Based on the results of the study showed that the motivation at PT. Semen Baturaja (Persero) does not need to be held because employees have self-motivation, and to increase employee motivation, incentive money is needed for those who excel. 4). Simultaneously (Test F) Variables Work Situation, Job Satisfaction, and Work Motivation have a significant influence on the performance of employees at PT. Semen Baturaja (Persero). It is known from the p value less than 0.05.